Waist Circumference Is More Closely Associated with Hypogonadism than Is Hyperglycemia, Independent of BMI in Middle-Aged Men - Po-Sheng Hsu; Chia-Lien Hung; Shih-Kai Tu; Hsin-Hung Chen; Deng-Ho Yang; Chun-Cheng Liao (Journal of Diabetes Research)
Introduction. To evaluate whether waist circumference (WC) or hyperglycemia is more closely associated with hypogonadism in middle-aged men. Research Design and Methods. This cross-sectional study analyzed male participants under 65 years old from the MJ Health Screening Center in Taiwan from 2007 to 2016. Basic patient characteristics with relevant parameters were obtained. We used the chi-square test to perform a correlation analysis for HbA1c and WC between participants with and without hypogonadism. A one-way ANOVA with post hoc Scheffe’s method was applied to compare the mean testosterone (T) among the HbAlc and WC groups (normal blood sugar with normal WC (NBSNW), abnormal blood sugar with normal WC (ABSNW), normal blood sugar with abnormal WC (NBSAW), and abnormal blood sugar with abnormal waist circumference (ABSAW)). Results. The 5,680 participants were divided into two groups based on the presence (n=599) or absence of hypogonadism (n=5,081), which was defined as total testosterone TT<300 ng/dL. The mean TT of group NBSAW (443.71±220.59 ng/dl) was significantly lower than that of group ABSNW (506.64±191.08 ng/dl, p<0.001). Moreover, the mean TT of group ABSAW (398.89±146.24 ng/dl) was significantly lower than that of group ABSNW (506.64±191.08 ng/dl, p<0.001). The ORs after adjusting for BMI, TG, HDL, SBP, and DBP were statistically significant when comparing NBSAW vs. NBSNW (OR=2.846; 95%CI=2.266–3.575; p<0.001), ABSNW vs. NDNW (OR=1.693; 95%CI=1.309–2.189; p<0.001), and ABSAW vs. NBSNW (OR=4.613; 95%CI=3.634–5.856; p<0.001). Conclusion. The current study showed that WC should be the risk factor that is more closely associated with hypogonadism than hyperglycemia in middle-aged men.